(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The author of the article formulated the task of energy balance optimization in Ukraine and determined the necessary prerequisites for its formation. It is established that the absence of a wide practical application of the theory of energy economics has led to a number of fundamental problems in public administration that have worsened in 2014-2017. The conclusion is made that the problem of the lack of energy balances necessary for the government can be solved by modernizing the energy statistics taking into account international recommendations and implementing an integrated system for complex energy monitoring and determined of energy security level. At the same time, the task of optimizing the energy balance should be included in the "tree of goals" of the Energy Strategy of Ukraine until 2035. Optimization of the energy balance as a component of the formation of an energy-efficient society in Ukraine should be carried out in accordance with the principles of protecting national interests, diversification, interchangeability of energy resources, environmental acceptability, economic efficiency, rational consumption, balance of interests and others. As a limitation in the task of optimizing the balance, a given level of energy security should be used, which takes into account the structure of regional energy supply and consumption, as well as the transition period to this level. As the objective function, it is necessary to take the project cost, which is determined in stages, but is minimized for the project as a whole. Optimization of the energy balance of Ukraine should be conducted, guided by the criteria of efficiency and effectiveness. At the same time, each consumer should be able to use different sources of fuel and energy at different times. Fuel and energy production should be decentralized. Energy flows should be disaggregated. In each region, an energy reserve should be created, which combines the fuel stocks of all kinds and the electric power reserve. Thus, the proposed approach provides for the creation of a multi-vector, mosaic energy sector that takes into account the priority areas of national and regional energy supply. The first step in its implementation should be the establishment of transparent, understandable, stable, equal "rules for the game" for all actors in the energy markets, and the predictable evidence-based policy making.